Comparative Proteome Analysis of Shewanella putrefaciens WS13 Mature Biofilm Under Cold Stress - Yan, Jun; Xie, Jing (Frontiers in Microbiology, 2020)
Shewanella putrefaciens is wide spread psychrotrophic Gram-negative bacteria and have been identified as the dominant spoilage microorganism of seafood during cold storage, causing the reduction of shelf-life and loss of foodstuffs. S. putrefaciens can easily attach on the biotic/abiotic surfaces and form biofilm. The formation of biofilm is conducive to their survival and the spoilage of the seafood. The aim of the study was to investigate the biofilm formation characteristic of S. putrefaciens under different incubation temperatures (4, 15 and 30 o C). The biofilm characteristic were evaluated by using crystal violet staining and confocal laser scanning microscopy (CLSM). Moreover, the chemical composition of the mature biofilm was analyzed by Raman spectroscopy (RM), then a comparative proteomic analysis was performed to investigate metabolic pathways and protein determinants of underlying mature biofilm formation of Shewanella putrefaciens under cold stress. In conclusion, this work contributes to a better understanding of the biofilm formation mechanism of psychrotrophic spoilage bacteria at low temperature and provides a theoretical basis for the elimination of biofilm further controls of spoilage microorganism contamination of aquatic products during the preservation and processing. ,